Management of the inpatient with heart failure in an internal medicine ward - Joaquim, Luis Fernando; Volpe, Gustavo J.; Figueiredo, Alexandre B. de; Moriguti, Julio C. (Medicina (Ribeirao Preto), 2010)
The increasing prevalence in heart failure and associated nonadherence of patients to the proposed ambulatory-treatment regimen cause the decompensate clinical picture to be the cornerstone of the high incidence of hospitalization found in such disorder, which brings a greater impact in public health. The purpose of the present study is to establish a protocol to be applied to heart failure inpatients at an internal medicine ward, such as the Hospital Estadual de Ribeirão Preto (SP, Brazil), in order to guarantee complete recovery from acute decompensated heart failure, as well as to reassure that patients understand the importance of following the proposed treatment protocols. Accordingly, pharmacological therapy and nonpharmacological strategies will be either reintroduced or optimized, in order to reduce the period of hospitalization, rate of infirmary readmission, and also to favor a better ambulatory follow-up of these patients.